2009
DOI: 10.1208/s12249-009-9197-2
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam-Loaded Solid Lipid Nanoparticles: Design and Characterization

Abstract: The aim of the present study was to investigate the feasibility of the inclusion of a water-insoluble drug (diazepam, DZ) into solid lipid nanoparticles (SLNs), which offer combined advantages of rapid onset and prolonged release of the drug. This work also describes a new approach to prepare suppositories containing DZ-loaded SLN dispersions, as potential drug carrier for the rectal route. Modified high-shear homogenization and ultrasound techniques were employed to prepare SLNs. The effect of incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(94 citation statements)
references
References 30 publications
11
78
0
3
Order By: Relevance
“…This is in agreement with reports by Abdelbary et al and Kumar et al 42,43 The higher %EE and %DL found in formulations containing stearic acid either alone or in combination with other lipid material is obvious, and can be explained by the higher solubility of sulpiride in acids. 2,44 This was confirmed by the rapid dissolution of sulpiride in melted stearic acid during the preparation of SLN.…”
supporting
confidence: 93%
“…This is in agreement with reports by Abdelbary et al and Kumar et al 42,43 The higher %EE and %DL found in formulations containing stearic acid either alone or in combination with other lipid material is obvious, and can be explained by the higher solubility of sulpiride in acids. 2,44 This was confirmed by the rapid dissolution of sulpiride in melted stearic acid during the preparation of SLN.…”
supporting
confidence: 93%
“…7 Furthermore, the ITZ-NLCs had a lessordered crystal structure, which would contribute to a higher drug-loading capacity. 39 A similar finding was reported by Chen et al for the XRD analysis of ITZ-loaded nanoparticles with human serum albumin. 7 The XRD of ITZ powder also showed sharp peaks, which demonstrated the existence of crystalline ITZ.…”
Section: Xrd Studysupporting
confidence: 82%
“…The data clearly showed that higher concentration of oil phase surfactant caused higher DL/EE and decreased the mean size of the SLNs. This notion previously has been shown (Abdelbary & Fahmy, 2009). This fact may attribute to the reduction of surface tension with higher lipophilic surfactant content that may lead to smaller particles (Hu et al, 2005).…”
Section: Discussionmentioning
confidence: 54%